Exploring translanguaging praxes in Pakistani multilingual ESL classrooms of first-year students at university level - Atta, Aqsa; Naqvi, Swaleha Bano (Penerbit Universiti Kebangsaan Malaysia, 2022)
Though the use of L-1 in multilingual ESL classrooms is abandoned; recent research suggests the significance of using a complete linguistic repertoire. The use of a complete linguistic repertoire implies the free use of all kinds of knowledge of languages. It is linked with translanguaging, which involves the use of two languages in a fluid way to organize mental processes in learning. Adopting the framework of translanguaging and theory of language mode this study has identified the specific ESL classroom situations where students used their complete linguistic and semiotic repertoire during English reading and writing, particularly and during general interaction in the classroom. Moreover, it also explores the motives behind the use of complete linguistic repertoire in identified situations. The data for this experimental study were collected through field notes of classroom observations, video recordings during the intervention, and interviews of teachers and students after the intervention. The findings show that students use their complete linguistic repertoire to negotiate meaning, develop metalinguistic awareness and communicate fearlessly and without anxiety in various situations like brainstorming, outlining, instructions, question statements, jokes, and normal interaction with a teacher and their pairs. The study concludes that by paying attention to the mentioned specific situations, teachers may opt for translanguaging pedagogy in their lesson plans to enhance the L-2 learning process.